Bridging the Gap between Soft Skills and Language Acquisition for Employability: Vocational Education and Training as a Case Study - Ettaouass , Mohammed (Revue Internationale du Chercheur, 2025)
Amidst recent royal and governmental amendments advocated for enhancing vocational education, His Majesty King Mohammed VI, in his latest Royal Speech, emphasized the essential and paramount role of vocational education and training (VET) in producing individuals who are adequately adept enough for various sectors of the Moroccan workforce. In line with such vision, this study seeks to thoroughly dissect how VET can bridge the gap between soft skills and language acquisition to further enhance employability. Vocational education is fundamental in equipping students with practical skills, yet the development of complementary competencies remains underexplored in academia. It is in such research gap that this study intervenes, investigating how vocational education can integrate both foreign language proficiency and soft skills to better prepare students for the demands of the modern workplace. Through a mixed case study approach, integrating both quantitative surveys and qualitative interviews, this scrutiny explores the effectiveness of pedagogical methods that foster these skills simultaneously. The research objectives are achieved by gathering insights from the sampled participants ⸺both students and educators⸺ within vocational settings, enabling this study to put to the forth the unprecedented opportunities of incorporating language learning alongside soft skills development. The research findings aim to provide guidance for VET institutions to design more holistic curricula that prepare graduates with the essential skills needed to succeed in their careers, aligning with the evolving workforce demands.